2020
DOI: 10.1016/j.amjmed.2019.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Solutions to Ambulatory Faculty Recruitment, Retention, and Remuneration in Graduate Medical Education: An AAIM Position Paper

Abstract: AAIM is the largest academically focused specialty organization representing departments of internal medicine at medical schools and teaching hospitals in the United States and Canada. As a consortium of five organizations, AAIM represents department chairs and chiefs; clerkship, residency, and fellowship program directors; division chiefs; and academic and business administrators as well as other faculty and staff in departments of internal medicine and their divisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…The factors that were reported by the men in this study were factors that were also reported by female faculty in previous studies. [6][7][8][9][10]12 Factors that attracted men to the nursing faculty role included the opportunity to work with students, helping to shape the nursing profession, and encouragement by nurse faculty consistent with other studies. [6][7][8] Nurse faculty role modeling was a factor that was reported in this study as a top factor for attracting men to the nursing faculty role.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The factors that were reported by the men in this study were factors that were also reported by female faculty in previous studies. [6][7][8][9][10]12 Factors that attracted men to the nursing faculty role included the opportunity to work with students, helping to shape the nursing profession, and encouragement by nurse faculty consistent with other studies. [6][7][8] Nurse faculty role modeling was a factor that was reported in this study as a top factor for attracting men to the nursing faculty role.…”
Section: Discussionmentioning
confidence: 99%
“…These are the same strategies identified in prior studies. 6,8,10 Having discussions in undergraduate and graduate nursing programs about becoming a faculty member and offering grants and scholarships for faculty were important in this study. However in earlier studies by Arian et al 9 and Lee et al, 12 neither of these strategies were discussed regarding recruitment of faculty.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These factors may also play a significant role in retention of faculty members. Solutions to recruit, retain and maintain academic faculty members in Medical Education shows the need to consider various diversified factors (Lo et al, 2020). Specific study towards improved retention of nursing faculty from minority community shows the need to integrate various cross-cultural and peer mentoring into the academic environment (Julion et al, 2019).…”
Section: Introductionmentioning
confidence: 99%